2019
DOI: 10.3390/atmos10040225
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Along-Valley Orographic Variations on the Dispersion of Passive Tracers in a Stable Atmosphere

Abstract: A numerical model is used to investigate the transport of passive tracers in an idealized Alpine valley during stable wintertime conditions after the evening transition. The valley is composed of an upstream-valley section, which opens on a narrower downstream valley section, which opens onto a plain. The ratio between the valley-floor widths of the upstream and downstream sections is either 4 (simulation P1) or 11.5 (P2). The change in the thermal structure of the atmosphere in the along-valley direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Since recirculation is a kind of eddy, orographic features, such as valleys, favour these processes. Quimbayo-Duarte et al [ 58 ] analysed the air flow in a valley with two sections and observed recirculations when the air from the slopes converges at the valley floor and flows to the narrow section in the up-valley direction.…”
Section: Mesoscalementioning
confidence: 99%
“…Since recirculation is a kind of eddy, orographic features, such as valleys, favour these processes. Quimbayo-Duarte et al [ 58 ] analysed the air flow in a valley with two sections and observed recirculations when the air from the slopes converges at the valley floor and flows to the narrow section in the up-valley direction.…”
Section: Mesoscalementioning
confidence: 99%
“…The present study falls between idealized (e.g. Lehner and Gohm, 2010;Lang et al, 2015;Leukauf et al 2016;Quimbayo-Duarte et al, 2019) and real-case (e.g., Martínez et al, 2010;Jiménez and Cuxart, 2014;Jiménez et al, 2019) studies as we consider a realistic orography and a simplified initialization of the atmosphere. The use of a realistic orography is necessary as it greatly modulates local thermally driven flows (Rucker et al, 2008;Duine et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The inversion layer, typical of these wintertime episodes, along with topographic effects, leads to the formation of stagnation and ventilation zones [50,51]. In the sections of the valley displaying a nearly basin-like structure, stagnation zones develop in which pollutants travel over short distances from their emission points [11,52].…”
Section: Weak Synoptic Forcing and Thermally Driven Flowsmentioning
confidence: 99%